Strengthening healthcare through family medicine training in The Gambia: The journey so far - Abraham N. Gyuse; Iorfa Tor-Anyiin; Joshua P. Mwankwon; Ousman Nyan; Horeja Saine (AOSIS, 2024)
According to the World Health Organizations (WHO) family medicine forms the bedrock upon for accessible, affordable and equitable healthcare for any country. The need for family doctors is more acute for low income countries like The Gambia. More so that The Gambian health infrastructure is suboptimal and appropriate health personnel is low. This is worsened by brain drain leading to poor health indices. Despite these challenges and more, the department of Family Medicine was accredited for training in the Gambia with improved infrastructure (at the training centre), with 7 residents. Though there are still challenges there are also opportunities and strengths. There is therefore hope that the right personnel will be produced for an improved Gambian health system.